Fuzzy States and Complex Trajectories Observation, modelisation and interpretation of life histories (Méthodes et Savoirs, 2009)
Individuals experience a variety of different events throughout their life-course - birth, marriage, change of employment, school graduation, etc. - which sometimes occur in rapid succession, and whose timing and definition may seem unclear. Now that survey questionnaires are able to record individual trajectories in greater depth, changes of status can no longer be viewed simply as separate events, but involve a transition process of variable duration. The observation, modelling and interpretation of these fuzzy thresholds between two situations constitute a dynamic field of research in the social sciences. The authors of this manual have pooled their experience of event-history data collection to address the questions of "focus", i.e. finding the right observation distance to grasp the complexity of life histories, and of time, i.e. choosing the right timescale of detailed information collection. After analysing the links between quantitative and qualitative data, addressing the distinction between facts and perceptions, and deconstructing analysis data categories, they offer a number of conceptual and methodological solutions. This study extends beyond the scope of specific examples to develop a major empirical approach in a still largely unexplored area. This book targets a much broader audience than the community of demographers alone. It concerns everyone in the field of social sciences who, at one moment or another, is required to organize data collection in the field, either for research or practical purposes. The Groupe de réflexion sur l'approche biographique (GRAB) brings together researchers and academics from a range of institutions (INED, IRD, CNRS, etc.) working in a variety of disciplines: demography, geography, sociology, economics, etc. It is building on the experience acquired through 25 event-history surveys conducted to date in France, Africa and Latin America.